2017
DOI: 10.1016/j.ccell.2017.09.007
|View full text |Cite
|
Sign up to set email alerts
|

A p53 Super-tumor Suppressor Reveals a Tumor Suppressive p53-Ptpn14-Yap Axis in Pancreatic Cancer

Abstract: SUMMARY The p53 transcription factor is a critical barrier to pancreatic cancer progression. To unravel mechanisms of p53-mediated tumor suppression, which have remained elusive, we analyzed pancreatic cancer development in mice expressing p53 transcriptional activation domain (TAD) mutants. Surprisingly, the p5353,54 TAD2 mutant behaves as a “super-tumor suppressor”, with an enhanced capacity to both suppress pancreatic cancer and transactivate select p53 target genes, including Ptpn14. Ptpn14 encodes a negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
158
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(163 citation statements)
references
References 71 publications
5
158
0
Order By: Relevance
“…By using an HPV16 E7 variant that cannot degrade PTPN14 (Figures 1 and 2) and by directly testing the effect of PTPN14 knockout in primary HFK (Figure 4), we determined that PTPN14 loss results in a downregulation of several markers of epidermal cell differentiation. Consistent with this idea, PTPN14 appears to be a target of regulation by p53 in mouse cells, but is likely a p63 target in human cells (79, 8688). p63 is a master regulator of epidermal development (89).…”
Section: Discussionmentioning
confidence: 58%
“…By using an HPV16 E7 variant that cannot degrade PTPN14 (Figures 1 and 2) and by directly testing the effect of PTPN14 knockout in primary HFK (Figure 4), we determined that PTPN14 loss results in a downregulation of several markers of epidermal cell differentiation. Consistent with this idea, PTPN14 appears to be a target of regulation by p53 in mouse cells, but is likely a p63 target in human cells (79, 8688). p63 is a master regulator of epidermal development (89).…”
Section: Discussionmentioning
confidence: 58%
“…5), we determined that PTPN14 loss results in a downregulation of several markers of epidermal cell differentiation. Consistent with this idea, PTPN14 appears to be a target of regulation by p53 in mouse cells but is likely a p63 target in human cells (79,(86)(87)(88). p63 is a master regulator of epidermal development (89).…”
Section: Discussionmentioning
confidence: 71%
“…Our previous finding that PTPN14 is targeted for degradation by high-risk HPV E7 but not by low-risk HPV E7 suggested that PTPN14 loss might be related to the biology of the high-risk HPV (47). PTPN14 is a candidate tumor suppressor based on the observation that it is mutated in some cancers (54,57,(78)(79)(80)(81). The targeted degradation of PTPN14 by high-risk HPV E7 requires the E3 ubiquitin ligase UBR4 and the interaction of UBR4 with papillomavirus E7 is required for E7 to transform cells (45,46).…”
Section: Discussionmentioning
confidence: 99%
“…Yap-1 is crucial in promoting pancreatic tumorigenesis 31 . Yap-1 is activated in p53 deficient tumors and p53 is mutated in about 75% of PDAC patients 32 . Yap-1 expression promotes cell cycle proliferation as well as invasion and migration.…”
Section: Discussionmentioning
confidence: 99%